2019
DOI: 10.1002/ece3.5613
|View full text |Cite
|
Sign up to set email alerts
|

The influence of different aspects of grouse moorland management on nontarget bird assemblages

Abstract: Conflict between stakeholders with opposing interests can hamper biodiversity conservation. When conflicts become entrenched, evidence from applied ecology can reveal new ways forward for their management. In particular, where disagreement exists over the efficacy or ethics of management actions, research clarifying the uncertain impacts of management on wildlife can move debates forwards to conciliation. Here, we explore a case‐study of entrenched conflict where uncertainty exists over the impacts of multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The impact of land management interventions (e.g. rotational moorland burning) on Curlew abundance has previously been studied in upland habitats (Douglas et al, 2014, Littlewood et al, 2019. Here, for the first time, we have shown that physical ground-disturbance, which is advocated as a conservation measure within lowland dry grassland and grass-heath for many rare, scarce and threatened species (Fuller et al, 2017;Hawkes et al, 2019a,b), also provides suitable Curlew nesting habitat, with no reduction in nest survival.…”
Section: Conservation Implicationsmentioning
confidence: 59%
“…The impact of land management interventions (e.g. rotational moorland burning) on Curlew abundance has previously been studied in upland habitats (Douglas et al, 2014, Littlewood et al, 2019. Here, for the first time, we have shown that physical ground-disturbance, which is advocated as a conservation measure within lowland dry grassland and grass-heath for many rare, scarce and threatened species (Fuller et al, 2017;Hawkes et al, 2019a,b), also provides suitable Curlew nesting habitat, with no reduction in nest survival.…”
Section: Conservation Implicationsmentioning
confidence: 59%
“…Tharme et al 2001), especially from legal predator control (e.g. Fletcher et al 2010, Littlewood et al 2019, there are also some negative effects. Species reported to show positive effects include Red Grouse and some waders, especially European Golden Plover Pluvialis apricaria and Eurasian Curlew Numenius arquata (e.g.…”
Section: )mentioning
confidence: 99%
“…Species reported to show positive effects include Red Grouse and some waders, especially European Golden Plover Pluvialis apricaria and Eurasian Curlew Numenius arquata (e.g. Tharme et al 2001, Littlewood et al 2019. On the other hand, Newton (2021) concludes that raptor persecution on grouse moors is so widespread and intense that it affects population levels, including of Hen Harrier and Peregrine Falcon Falco peregrinus, both on and beyond grouse moors.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies directly focus on the impacts of burning on birds and rather focus on the impacts of grouse moor management or vegetation structure in general Tharme et al, 2001;Calladine et al, 2014;Douglas et al, 2017). The influence of different aspects of grouse moorland management on bird assemblages were assessed by Littlewood et al, (2019) and found a positive relationship between the abundance of three ground nesting birds (Golden Plover -Pluvialis apricaria Linnaeus, Curlew -Numenius arquata Linnaeus and Common Snipe -Capella gallinago Linnaeus) and predator control. Evidence for the effects of burning on the same three species were, however, weak (Littlewood et al, 2019).…”
Section: Vulpes Vulpes Linnaeus Stoat -Mustela Ermine Linnaeus Cow -Corvus Coronementioning
confidence: 99%